Abdul Haseeb Ansari, Comparative Jurisprudence: a comparative appraisal of Western jurisprudence and Islamic jurisprudence (2018) - Ahmad, Muhamad Hassan (Serials Publications (P) Ltd., 2018)
The book entitled Comparative Jurisprudence: A Comparative Appraisal of Western Jurisprudence and Islamic Jurisprudence fills the matrix where there was a gap until publication of this book. There existed host of scholarly work in the form of book and articles on Western jurisprudence and Islamic jurisprudence, but there were scarce of intellectual exercise of this kind. Prof. Dr. Abdul Haseeb Ansari, a senior Professor at the Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia (IIUM) has made an incredible intellectual endeavor to venture into almost unexplored field of research, which was actually demanded by comparative law scholars, and which will be certainly esteemed by them. The book reflects his protracted teaching experience and insight in the matters discussed in various chapters. The book is thus quite pertinent and useful.